(3eVGgGI GdCchGfs - (3bGSe Hf YHO GdQMef Hf MSf GdSYOj GdbGOQj GdTGaYj GdMdHj, CHh GdaVd,J (B982 (3g` s
(3ChdgG (B:s
(3hbPa aj bdhHge ef ajV CfhGQ GdJhMjO eG jLQj aJGQI jbPa aj GdbdH EdgGeoG s
(3BNQgG (B:s
(3hgh YGde GdCSQGQ aGage CjOc Gddg HGdage, JeJ GdQSGdI GdoeSeGI eVGgGJ GdCchGf ajeG jbGHdg ef GdEfSGf hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg hSde s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B105 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B832s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJUha hGdBOGH GdTQYjIs